Tradisi Pemakaman Mepasah Desa Terunyan Dalam Kajian Historis - Rosyida, Shela Zaimatur; Listiani, Intan Dwi; Mevia, Nia Ayu; Salma, Afin Naila; Khozin, Nurwildan Tsalits; Niswatin; Segara, Nuansa Bayu (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
The Mepasah funeral tradition in Trunyan Village, Bali, is a unique cultural heritage of the Bali Aga community that has survived since the time of Ancient Bali. Unlike the common Balinese Hindu funeral practice of cremation, the Trunyan community treats the body by leaving it lying on the ground under the Taru Menyan tree without burying it. This tradition not only serves as a form of respect for death, but also reflects the philosophy of life of the local community that upholds harmony between humans, nature, and ancestral spirits, as reflected in the concept of Tri Hita Karana. This research aims to historically examine the origins, development, and continuity of the Mepasah tradition in the midst of modernization, and explore the main reasons that make the Trunyan community still maintain it today. This research uses a qualitative approach with historical methods. The results of the study show that despite the influence of tourism and globalization, the Trunyan community collectively maintains this practice as a cultural identity as well as an irreplaceable spiritual system. In addition, support from customary institutions, selectivity in accepting change, and active involvement of the younger generation in preservation make this tradition sustainable. These findings emphasize the importance of historical and cultural approaches in understanding and preserving local cultural practices so that they do not lose their original meaning in the midst of changing times.